Designing an Android-Based Streaming Video Player Application - Gatot Soepriyono (Institute of Computer Science (IOCS), 2020)
Indonesia is one of biggest country that has a huge potential. Nowday, mobile technology is growing very rapidly. Therefore, we also have to keep following these technological developments. For example, many software of video players run on Android-based OS. The author interested in making an Android-based Video Player Streaming application using the Eclipse Kepler application. Using the Waterfall method, which is a method of sequential requirement (system analysis), system design, coding, testing, implementation and maintenance. How to install JRE, JDK, SDK, and Streaming Video Player source code, finally the author produced a video player that can be run on the Android mobile operating system, and smartphone tablets Ice Cream Sandwich and Jelly Bean. The added value of this application is able to play video live streaming. The author will continue to develop this application. So, it can be operated on the i-phone operating system, i-pod and other types according to the progress of the operating system itself.